Improved Gait of Persons With Multiple Sclerosis After Rehabilitation: Effects on Lower Limb Muscle Synergies, Push-Off, and Toe-Clearance - Jonsdottir, Johanna; Lencioni, Tiziana; Gervasoni, Elisa; Crippa, Alessandro; Anastasi, Denise; Carpinella, Ilaria; Rovaris, Marco; Cattaneo, Davide; Ferrarin, Maurizio (Frontiers in Neurology, 2020)
Introduction Persons with MS (PwMS) have markedly reduced push-off and toe-clearance during gait compared to healthy subjects (HS). These deficits may result from alterations in neuromotor control at the ankle. To optimize rehabilitation interventions for PwMS, a crucial step is to evaluate if and how altered neuromotor control, as represented by muscle synergies, improves with rehabilitation. In this study we investigated changes in ankle motor control and associated biomechanical parameters during gait in PwMS, occurring with increase in speed after gait rehabilitation. Methods 3D motion and EMG data were collected while 11 PwMS (age 50.3+11.1; EDSS 5.2+1.2) walked overground at self-selected speed before (T0) and after 20 sessions (T1) of intensive treadmill training. Muscle synergies were extracted using non-negative matrix factorization. Gait parameters were computed according to the LAMB protocol. Pearson's correlation coefficient was used to evaluate the similarity of motor modules between PwMS and HS. To assess differences in distal module activations after the gait rehabilitation (Forward Propulsion (FPM) and Ground Clearance modules (GCM)), each module's activation timing was integrated over 100% of the gait cycle and the activation percentage index (API) was computed in six phases. Ten age matched HS provided two separate speed-matched normative dataset for T0 and T1. For speed independent comparison for the PwMs Z scores were calculated for all their gait variables. Results In PwMS velocity increased significantly from T0 to T1 (0.74 to 0.90 m/sec, p<0.05). The activation profiles (API) of FPM and GCM of PwMS improved in pre-swing (p<0.05): FPM (Mean (95%CI) [%]: T0: 12.5 (5.7-19.3) vs T1: 9.0 (2.7-15.3)); GCM (T0: 26.7 (18.2-35.3) vs T1: 24.5 (18.2-30.7)). This was associated with an increase in toe clearance (80.3 to 103.6 mm, p<0.05) and a higher ankle power peak in pre-swing (1.53 to 1.93 W/Kg, p<0.05). Conclusion Increased gait speed of PwMS after intensive gait training was consistent with improvements in spatio-temporal gait parameters. The most important finding of this study was the re-organization of distal leg modules related to neurophysiological changes induced by rehabilitation. This was associated with an improved ankle performance.